Managing Transitions: Coping Strategies for New Principals in Colleges of Education, Ghana (International Journal of Scientific Research and Management (IJSRM), 2020)
Principals’ transition in Colleges of Education in Ghana is critical to quality teacher education and training, but it comes with complexities and challenges to newly appointed principals. However, there is a seeming absence of research on strategies for smooth transitions in Colleges of Education in Ghana. This study was therefore conducted to establish strategies that promoted the College of Education principals’ transition management in Ghana. Phenomenological research design was used for the study. Ten (10) newly appointed principals of public colleges of education were purposively sampled for the study. Interview protocol was the research instrument used. The data collected was analyzed using content analysis method. The study established that capacity building, relationship building, appropriate leadership style and maintenance of discipline were key among the coping strategies for smooth transitions. This study then provides a guide for new principals. It was recommended that this area should be further explored and a model for managing transition designed to support College of Education principals’ in transition.